The Effects Of Online Problem-Based Learning In Cloud Computing Environment On Performance And Critical Thinking Of Students With Different Self-Regulated Learning Levels In Learning Programming - Ali, Amira Saif Abdullah (2025)
Many challenges related to learning programming for novice learners in yemeni higher education. In addition, the conventional approach of education – which is still being widely used in yemen - often fail to assist them to become active learners during the learning process. Problem-based learning (pbl) might offer alternative solution to these problems. The current study attempted to investigate the effects of online pbl in a cloud computing environment on performance and critical thinking of 120 undergraduate students from a public university in yemen. This study involved an independent variable that consisted of the two learning methods, i.E. (a) problem-based learning (pbl) and (b) direct instruction (di), two dependent variables, i.E., the students’ performance and critical thinking, and self-regulated learning (srl) as the moderating variable. This study employed the sequential mixed methods design (quan and qual) which involved quantitative and qualitative phases. For the quantitative phase, a 2 x 2 factorial design quasi experimental study with pre-test and post-test control group design was applied. The students’ programming performance was measured through the computer programming performance test (cppt), their critical thinking was measured through the yoon's critical thinking disposition (yctd), while their srl level was measured by applying the online self-regulated learning questionnaire (oslq).